Discourses of exclusion on Twitter in the Turkish Context: #ülkemdesuriyeliistemiyorum (#idontwantsyriansinmycountry). (August 2020) - Erdogan-Ozturk, Yasemin; Isik-Guler, Hale
Abstract: The new communicative affordances of online spaces have transformed the ways and domains we build and negotiate meaning. At the same time, they have introduced diverse channels to produce and disseminate animosity. This article explores online discourses as new communicative environments characterized by their unique textual and semiotic features to unfold the discursive constructions of hate and hostility towards Syrian refugees in Turkey. Building on the principles of the Social Media Critical Discourse Studies (SM-CDS) framework proposed by KhosraviNik (2018) and the Discourse-Historical Approach (DHA) by Reisigl and Wodak (2001), the study analyzes a subset of tweets that includes the hashtag #ülkemdesuriyeliistemiyorum (#idontwantsyriansinmycountry) to understand its functions in constructing and proliferating an exclusionary discourse against refugees. The study focuses on referential, argumentation and intensification strategies used in tweets as well as their wider socio-political implications. The results reveal that refugees in Turkey are delineated as threats, invaders, criminals and potential dangers by the users of online media. It is further observed that a sharper rhetoric and a more intense negative-other representation emerge in Twitter as an online public space compared to print media discourses. While scrutinizing the (re)construction and representation of refugees, our analysis has also uncovered that hate and hostility discourses towards refugees constantly operate to build a collective nationalist identity. This interlocking relationship between constructing refugees through stereotypical attributes as a homogeneously dangerous group and forming a collective Turkish identity is manifested at each level of our analysis.